The effectiveness of the ecopreneurship model in increasing environmental awareness among college students - Haris, Risma; Nur, Syahban; Lutfi; Ali, Muhammad; Hafidah, Andi; Sartika S (Indonesian Research Journal in Education |IRJE|, 2025)
This research aims to determine the effectiveness of the ecopreneurship model in increasing environmental awareness among midwifery students. The research method was quasi-experimental, with a control group design using midwifery students as research subjects. The research stages include applying the ecopreneurship model in the learning process in the lecture hall, as well as measuring the level of knowledge before and after. A valid and reliable survey instrument was used to collect data regarding student perceptions and attitudes towards the environment. The data analysis results show that applying the ecopreneurship model significantly increases environmental knowledge and awareness among midwifery students. Previously, students tended to have a limited understanding of environmental issues and their relevance in the context of entrepreneurship education. However, after learning about the ecopreneurship model, there was a real increase in students' understanding, attitudes, and involvement towards environmental issues.